PENGARUH EFIKASI DIRI, MINAT KERJA, KEAKTIFAN ORGANISASI TERHADAP KESIAPAN KERJA MAHASISWA STIE SATYA DHARMA - Komang Trisna Sari Dewi; Kadek Tirta Yasa; I Komang Gde Trisna Purwantara (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Student job readiness is a crucial issue that must be addressed by higher education institutions, including the Satya Dharma College of Economics. Given this phenomenon, it is important to evaluate students' internal factors that can encourage job readiness, such as self-efficacy, work interest, and activeness in campus organizations. This study aims to analyze the influence of self-efficacy, work interest, and organizational activity on the job readiness of students at the Satya Dharma College of Economics. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through the SmartPLS 3.0 application. The number of respondents was 80 active students. The results show that self-efficacy, work interest, and organizational activity each have a positive and significant effect on student job readiness. Simultaneously, the three variables also have a significant effect with an R-square value of 0.921, which means that 92.1% of the variation in job readiness can be explained by these three factors. These findings indicate that student job readiness is strongly influenced by internal factors. Therefore, increasing self-efficacy, growing work interest, and active participation in organizations need to be continuously encouraged to produce competent graduates who are ready to compete in the world of work.